2017
DOI: 10.1123/jpah.2015-0700
|View full text |Cite
|
Sign up to set email alerts
|

Does Preschool Physical Activity and Electronic Media Use Predict Later Social and Emotional Skills at 6 to 8 Years? A Cohort Study

Abstract: Findings suggest that physical activity is not associated with children's psychosocial health while some types of electronic media use are. Future research should investigate the contexts in which preschoolers participate in these behaviors and potential causal mechanisms of associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 52 publications
0
36
1
3
Order By: Relevance
“…Reinecke 49 found that videogames are systematically used to recover from stressful situations: specifically, the tendency to do so was stronger in people with emotion focused than problem focused coping style. Hinkley et al 50 performed a longitudinal study to investigate the relationship among electronic media use of children (parent reported) and their social-emotional skills: results showed that videogames' play was positively associated with intrapersonal abilities, stress management skills, and global emotional quotient. Moreover, qualitative research on the topic 51 confirmed that gamers play also to alleviate and manage negative feelings; in terms of ''escapism,'' this could be related to videogames' properties that promote projective fantasy (e.g.…”
Section: Cross-sectional and Qualitative Studiesmentioning
confidence: 99%
“…Reinecke 49 found that videogames are systematically used to recover from stressful situations: specifically, the tendency to do so was stronger in people with emotion focused than problem focused coping style. Hinkley et al 50 performed a longitudinal study to investigate the relationship among electronic media use of children (parent reported) and their social-emotional skills: results showed that videogames' play was positively associated with intrapersonal abilities, stress management skills, and global emotional quotient. Moreover, qualitative research on the topic 51 confirmed that gamers play also to alleviate and manage negative feelings; in terms of ''escapism,'' this could be related to videogames' properties that promote projective fantasy (e.g.…”
Section: Cross-sectional and Qualitative Studiesmentioning
confidence: 99%
“…The way they use them, whether in individual or social context, is also a factor to consider. The frequent use of these devices in an individual context can accentuate psychosocial and socioemotional difficulties at the level of peer interaction or interpersonal skills (Hinkley, Timperio, Salmon, & Hesketh, 2017). Children's exposure to violent video games may exhibit aggressive behaviors which have a negative impact on the quality of interpersonal relationships.…”
Section: Influence Of Electronic Devices On Bullying Behaviorsmentioning
confidence: 99%
“…Studies addressing children's screen-time or content suggest that the content might have a greater influence on health outcomes in youth rather than the actual amount of screen-time (2,10). Few studies have reported test-retest reliability and validity results in screen time (TV, E-games and computers) questionnaire instruments (11)(12)(13). A few studies have included items to assess time spent on smartphones and tablets among toddlers or preschool children (14) (15) or adolescents (16) in order to quantify time spent on screen devices.…”
Section: Introductionmentioning
confidence: 99%